Direct experimental observation of mesoscopic fluorous domains in fluorinated room temperature ionic liquids. Issue 20 (10th May 2017) - Lo Celso, F.; Yoshida, Y.; Castiglione, F.; Ferro, M.; Mele, A.; Jafta, C. J.; Triolo, A.; Russina, O.
Abstract : Neutron scattering patterns reveal fluorinated nano-scale domain segregation in fluorinated room temperature ionic liquids. Abstract : Fluorinated room temperature ionic liquids (FRTILs) represent a class of solvent media that are attracting great attention due to their IL-specific properties as well as features stemming from their fluorous nature. Medium-to-long fluorous tails constitute a well-defined apolar moiety in the otherwise polar environment. Similarly to the case of alkyl tails, such chains are expected to result in the formation of self-assembled fluorous domains. So far, however, no direct experimental observation has been made of the existence of such structural heterogeneities on the nm scale. We report here the first experimental evidence of the existence of mesoscopic spatial segregation of fluorinated domains, on the basis of highly complementary X-ray and neutron scattering data sets (highlighting the importance of the latter probe) and NMR spectroscopy. Data are interpreted using atomistic molecular dynamics simulations, emphasizing the existence of a self-assembly mechanism that delivers segregated fluorous domains, where preferential solubilisation of fluorinated compounds can occur, thus paving the way for several smart applications.